Medical policy without scientific evidence: the promiscuity paradigm and AIDS - Murray, Stephen O.; Payne, Kenneth W. (Homosexuality and medicine, health and science)
"Stephen O. Murray; Kenneth W. Payne Fonds Suzan Daniel (FSD)"